Stature and mitigation systems affect the risk of leg injury in vehicles attacked under the body by explosive devices - Rebelo, Eduardo A; Grigoriadis, Grigoris; Carpanen, Diagarajen; Bull, Anthony M. J.; Masouros, Spyros (Frontiers in Bioengineering and Biotechnology, 2023)
A finite-element (FE) model, previously validated for underbody blast (UBB) loading, was used here to study the effect of anthropometry and of mitigation systems on injury risk to the lower limb. A range of potential UBB loadings were simulated. The risk of injury to the lower extremity was calculated when no protection was present, when a combat boot (Meindl Desert Fox) was worn, and when a floor mat (IMPAXXTM), which can be laid on the floor of an armoured vehicle, was added. The risk of injury calculated indicates that the floor mat provided a statistically significant reduction in the risk of a major calcaneal injury for peak impact speeds below 17.5 m/s when compared with the scenarios in which the floor mat was not present. The risk of injury to the lower extremity was also calculated for a shorter and a taller stature compared to that of the nominal, 50th percentile male anthropometry; simulations were run by scaling the tibia to that of the nominal stature. The results showed that there is a higher risk of injury associated with the short stature compared to the nominal and tall statures, whereas nominal and tall statures were statistically similar. These findings provide evidence that the combat boot and the floor mat have an attenuating effect, albeit limited to a range of possible UBB loads. The effect of stature on injury has implications on how vehicle design caters for all potential anthropometries. The observations offered by this compuational study are testament that finite-element analysis can be a powerful tool towards improving UBB safety technology and strategy, thus complementing laboratory and field experimental models of UBB.